2019
DOI: 10.1029/2019jc014937
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Satellite‐Derived Sea Surface Salinity Products from SMOS, Aquarius, and SMAP

Abstract: Global sea surface salinity (SSS) has been obtained from space since 2009 by the Soil Moisture and Ocean Salinity (SMOS) mission and has been further enhanced by Aquarius in 2011 and Soil Moisture Active‐Passive (SMAP) missions in 2015. Due to the differences between SMOS, Aquarius, and SMAP in the instruments used, retrieval algorithms, and error correction strategies, the quality of their gridded products are different. In this paper, we have assessed the accuracy of three satellite products using in situ gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
56
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(74 citation statements)
references
References 46 publications
5
56
0
3
Order By: Relevance
“…Within the Arabian Sea, there is a consistent improvement in SMAP statistical skills from the west, where the Gulfs of Aden and Oman are, to the east (Figure 8). Offshore the western boundary, all products show that SMAP captures SSS in the Arabian Sea with similar performance to the global evaluations [3,8], in which correlation in open water away from the coast is above 0.7 and rmsd was less than 0.2…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…Within the Arabian Sea, there is a consistent improvement in SMAP statistical skills from the west, where the Gulfs of Aden and Oman are, to the east (Figure 8). Offshore the western boundary, all products show that SMAP captures SSS in the Arabian Sea with similar performance to the global evaluations [3,8], in which correlation in open water away from the coast is above 0.7 and rmsd was less than 0.2…”
Section: Discussionmentioning
confidence: 58%
“…and histograms were calculated for each SMAP product for the collocated datasets to assess SMAP performance in the North Indian Ocean in both the spatial and temporal domains. These statistics are generally used in studies evaluating satellite salinity observations [1,3,8,9,12,13,[16][17][18]21,61].…”
Section: Collocation Between Smap and In Situ Observations And Statismentioning
confidence: 99%
“…[4]) which are commonly used for this purpose are derived from measurements at an average scale of 1 measurement per 3 • ×3 • square per 10 days. For the most part, validation of satellite SSS has been done comparing values to individual in situ measurements such as Argo floats [5][6][7]. Floats come to the surface in relatively random locations, and, if close enough in space and time, can be matched up with satellite samples [8].…”
Section: Introductionmentioning
confidence: 99%
“…The satellite estimate of an SSS snapshot at point E is equivalent to averaging the SSS over a region, the central part of which we will call the 'footprint'. in situ measurements such as Argo floats [5][6][7]. Floats come to the surface in relatively random locations, and, if close enough in space and time, can be matched up with satellite samples [8].…”
Section: Introductionmentioning
confidence: 99%
“…A number of other studies showed positive impacts due to the assimilation of SSS in controlled experiments, including improved upper ocean salinity (Vernieres et al, 2014), improved surface currents, mixed-layer depth, and barrier layer thickness (Chakraborty et al (2014(Chakraborty et al ( , 2015, and improved temporal variability of the vertical distribution of salinity in areas with large freshwater input (Seelanki et al, 2018). Still, the low temporal frequency of the data, large uncertainty estimates attributed to instantaneous observations, and large platform-specific biases (Bao et al, 2019), make the assimilation of SSS a continuing challenge. A nextgeneration technology that could produce SSS observations with the frequency, accuracy, and coverage of SST observations would be a high-impact capability.…”
Section: Prediction At Subseasonal To Seasonal Timescalesmentioning
confidence: 99%